Internal service quality, external service quality, employee Satisfaction and customer Satisfaction for Vietnamese hotels: A Theoretical Approach - Ha, Nguyen Thu; Anh, Cung Lan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 4, 2019)
In recent years, tourist accommodation establishments have been growing in both quantity and quality, making an important contribution to the development of tourism products, socio-economic development in local. Expected to 2020, Vietnam's economy will continue to witness the boom of the accommodation service business with more than 20 million foreign visitors visiting and the outstanding growth of the hotel service industry. The paper aims to examine the relationship between internal service quality, external service quality, and employee & customer satisfaction. Inheriting the domestic and foreign research results about service quality, customer satisfaction, combining the results of interviews with experts, group discussions with hotel administrators and tourists, the article proposed an analytical framework for internal service quality, external service quality, and employee & customer satisfaction for the hotels in Vietnam